2019
DOI: 10.3892/mmr.2019.10097
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA‑16 alters the response to inhaled β‑agonists in patients with asthma though modulating expression of ADRB2

Abstract: MicroRNAs (miRNAs) are non-coding RNAs of ~22 nucleotides in length, which serve an important role in numerous diseases. Asthma is a chronic airway inflammatory disease, which is the most common chronic disease among children. The role of miRNA (miR)-16 in asthma is unclear. The objective of the present study was to examine the underlying molecular mechanism of the involvement of miR-16 in asthma. A total of 72 volunteers diagnosed with asthma consented to participate in the study, of whom 52 participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…A negative correlation between lung function parameters and miR-16 in asthma was recently identified. 70 In silico analysis predicted Adrenoreceptor B-2 (ADRB2), which is involved in bronchial smooth muscle contraction, as a target gene for miR-16 and was later confirmed by luciferase assay. 70 Bioinformatic analysis of miRNA targets from the blood of house dust mite allergic asthmatic children revealed enrichment in the PI3K and NF-κB pathways.…”
Section: Asthmamentioning
confidence: 95%
“…A negative correlation between lung function parameters and miR-16 in asthma was recently identified. 70 In silico analysis predicted Adrenoreceptor B-2 (ADRB2), which is involved in bronchial smooth muscle contraction, as a target gene for miR-16 and was later confirmed by luciferase assay. 70 Bioinformatic analysis of miRNA targets from the blood of house dust mite allergic asthmatic children revealed enrichment in the PI3K and NF-κB pathways.…”
Section: Asthmamentioning
confidence: 95%
“…Recently, more detailed studies have identified potential miRNA targets, suggesting that multiple signaling processes may be affected. A negative correlation between lung function parameters and miR-16 in asthma was recently identified 70. In silico analysis predicted Adrenoreceptor B-2 (ADRB2), which is involved in bronchial smooth muscle contraction, as a target gene for miR-16 and was later confirmed by luciferase assay.…”
mentioning
confidence: 86%
“…Similar to miR-155, other miRNAs, such as miR-16, may function as a biomarker to predict responses to therapy in asthma [ 118 ] ( Table 2 ). In certain cases, miRNA expression levels differ based on asthma endotypes, such as neutrophilic or eosinophilic asthma [ 119 , 120 ] ( Table 2 ), showing associations with different clinical parameters.…”
Section: Exosomes In Biofluids In Asthmatic Inflammationmentioning
confidence: 99%